Antimicrobial therapy, resistance, and appropriateness in healthcare-associated and community-associated infections; a point prevalence survey. Issue 10 (October 2022) - Alsaedi, Asim A.; El-Saed, Aiman; Althaqafi, Abdulhakeem; Bhutta, Muhammad Javid; Abukhzam, Bassem; Alshamrani, Majid
Abstract: Background: Data examining differences in antimicrobial therapy and its appropriateness between healthcare-associated infections (HAIs) and community-associated infections (CAIs) are limited. The objective was to compare antimicrobial therapy, resistance, and appropriateness between CAIs and HAIs. Methods: One-day point prevalence survey targeting admitted patients with active infections was conducted in six tertiary care hospitals. Antimicrobial appropriateness was decided based on hospital antimicrobial guidelines, clinical assessment, culture results, and other relevant investigations. Results: Out of 1666 patient records reviewed, 240 (14.4%) infection events were identified. Prevalence of infections treated with antimicrobials were 6.5% for HAIs and 7.1% for CAIs. The most commonly prescribed antimicrobials were carbapenems (19.6%), cephalosporins (14.8%), and vancomycin (13.2%), with some differences between HAIs and CAIs. The overall contribution of MDR pathogens to both HAIs and CAIs was similar (34.0% versus 34.3%, p = 0.969). ESBL was significantly associated with CAIs while other gram-negative MDR pathogens significantly associated with HAIs. Overall appropriateness of antimicrobial therapy was similar in HAI and CAI events (64.2% versus 64.7%, p = 0.934). However, it was highest in aminoglycosides (78.6%) and lowest in vancomycin (40.8%). It was lowest in bloodstream infections than other infections (48.5% versus 61% to 78%, p = 0.044). Conclusion: Although the overall burden of MDR pathogens and appropriateness of antimicrobial therapy were similar in HAI and CAI events, there were some differences related to the type of MDR, type of antimicrobials, and type of infection. The current finding can guide training and educational activities of local antimicrobial stewardship initiatives aiming to improve antimicrobial therapy in hospital setting.